2021
DOI: 10.1007/s41347-021-00229-z
|View full text |Cite
|
Sign up to set email alerts
|

Differences between Facebook and Instagram Usage in Regard to Problematic Use and Well-Being

Abstract: Although the association of well-being (e.g., self-esteem, depression symptoms, and loneliness) with Facebook usage (i.e., number of friends and frequency of use) has been investigated by many researchers, only a limited number of studies have scrutinised Facebook against Instagram use. The aim of this study is not only to address this literature gap but also to explore whether problematic use and well-being differ between Facebook and Instagram users in relation to the number of received “likes” and Facebook … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…This cluster consisted of those individuals who spent significantly higher time on Instagram compared to Facebook or WhatsApp. These results align with previous findings, which found that Instagram users had substantially more problematic usage behavior than Facebook users [ 79 ]. The behavior of people in this cluster may be explained based on CUIT, where individuals may use Instagram excessively to compensate for poor self-esteem or a lack of feeling of self-worth [ [85] , [86] , [87] ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This cluster consisted of those individuals who spent significantly higher time on Instagram compared to Facebook or WhatsApp. These results align with previous findings, which found that Instagram users had substantially more problematic usage behavior than Facebook users [ 79 ]. The behavior of people in this cluster may be explained based on CUIT, where individuals may use Instagram excessively to compensate for poor self-esteem or a lack of feeling of self-worth [ [85] , [86] , [87] ].…”
Section: Discussionsupporting
confidence: 92%
“…The social networking cluster consisted of those who spent significantly more time on Facebook. These results further support the idea of [ 79 ], who studied the difference in problematic usage between Instagram, and Facebook using the Bergen Social Media Addiction Scale [ 80 ], and reported that Instagram users had substantially more problematic usage behavior than Facebook users. A possible explanation for the behavior of people in this cluster may be based on the I-PACE model [ 52 ].…”
Section: Discussionsupporting
confidence: 87%
“…One of the reasons that may explain the difference between the original version and the Portuguese version is the fact that there are seven years between one version and the other. As a result, there have been: (1) numerous changes in the social media themselves (Kane, 2017), with the development of new services on each social media (Limniou et al, 2021); (2) new social media have appeared with a new and different ethos from the existing ones (Bryant et al, 2019); (3) the meaning (Hadley, 2017) and role of social media have changed (Zolkepli & Kamarulzaman, 2015); (4) social media users do not share the same profile as users seven years' ago (Hunter et al, 2018). Besides these aspects, the significant changes in the content and structure of a scale focusing on the dimensions of salience (e.g., Frequency or intensity of use), compulsivity/emotion regulation, or social consequences characteristic of addictive behaviors may be the harbinger of the differentiation between substance and behavioral addictions.…”
Section: Discussionmentioning
confidence: 99%
“…The displacement hypothesis [28,40] and the I-PACE model [39,41] explain the mediating role of loneliness in the relationship between Instagram addiction and low life satisfaction. Some previous studies showed that SMU is a positive predictor of loneliness [15,16,31,36,[42][43][44], while other research indicated a negative relationship [24,[45][46][47] or no significant association [48]. In addition, active and not intensive SMU was a positive predictor of life satisfaction [17,46], while excessive and passive SMU was negatively related to wellbeing [11][12][13][14][15][16][17].…”
Section: The Current Studymentioning
confidence: 91%
“…Some previous studies showed that SMU is a positive predictor of loneliness [ 15 , 16 , 31 , 36 , 42 , 43 , 44 ], while other research indicated a negative relationship [ 24 , 45 , 46 , 47 ] or no significant association [ 48 ]. In addition, active and not intensive SMU was a positive predictor of life satisfaction [ 17 , 46 ], while excessive and passive SMU was negatively related to well-being [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%